POLYSEMY IN COGNITIVE LINGUISTICS - Dalieva Madina Xabibullaevna (American Journals, 2023)
This research presents an analysis of the deep language factors that predetermine polysemy of English from the cognitive point of view. In line with a well-established point of view in cognitive linguistics, this study treats the semantics of a word as a two-level phenomenon possessing the semantic (external) level and the conceptual (internal) level. Unlike traditional research into polysemy inside historical and lexical semantics, cognitive analyses go beyond words and polysemy is regarded as a cognitive organizing principle shared by other areas of language, such as morphology, phonology and syntax.
Keywords: cognitive, polysemy, linguistics, investigation, language, syntax